The Preaching of the Third Crusade (1187-1192): The Early University of Paris, Biblical Exegesis, and the Coming Apocalypse - Marx, Alexander (Commentaria, 2025)
This book offers the first broad investigation of the preaching and mobilization of the Third Crusade (1187-92), straddling around 200 sermon texts as well as 100 manuscripts. It addresses the major problem that “crusade sermon” is an anachronistic category; therefore, it develops methodological tools for determining “crusade potential” in the many sermons that survived from the Middle Ages. As a result, both the medieval and the modern historiography are contested: the sermon texts tell us a story that is different in many ways. Dieses Buch bietet die erste breite Untersuchung zur Predigt und Mobilisierung des Dritten Kreuzzuges (1187-92), indem es rund 200 Predigttexte, sowie rund 100 Handschriften berücksichtigt. Es setzt sich mit dem zentralen Problem auseinander, dass „Kreuzzugspredigt“ eine anachronistische Kategorie ist, und entwickelt daher methodische Ansätze, um „Kreuzzugspotential“ in den vielen überlieferten Predigten des Mittelalters festzumachen. Auf diese Weise wird sowohl die mittelalterliche als auch die moderne Historiographie infrage gestellt, da uns Predigttexte eine in vielerlei Hinsicht andere Geschichte erzählen.